Hospitalization for Community-Acquired Pneumonia in Alberta Patients with Human Immunodeficiency Virus Infection: A Case Control Study - David H Johnson; Keumhee C Carriere; Stan Houston; Yan Jin; Gerry Predy; John Gill; Stephen Shafran; Thomas J Marrie (Canadian Respiratory Journal)
BACKGROUND: To determine whether outcomes of pneumonia among human immunodeficiency virus (HIV)-positive persons differed from those among HIV-negative persons.